Bimbingan Belajar Sebagai Upaya Mengatasi Kesulitan Belajar Siswa - Khairunisa; Husna Ayudia Salsabila; Tasya Desrindra Putri Dlm; Gusman Lesmana (STID Raudlatul Iman Sumenep, 2024)
Various efforts have been made by the government in improving the quality of education in Indonesia both in quality and quantity. This effort is carried out starting from the level of elementary education to tertiary institutions. Law No. 20 of 2003 on the National Education System states that